Effects of temperature on sperm motility of burbot Lota lota: spontaneous activation and calcium dependency - Dadras, Hadiseh; Boryshpolets, Sergey; Golpour, Amin; Policar, Tomas; Blecha, Miroslav; Dzyuba, Borys (Journal of fish biology, 2019)
Several factors regulating activation of spermatozoon motility in Eurasian burbot, Lota lota, including osmolality, calcium (Ca2+ ) ions, and temperature were investigated. Spermatozoon motility in Eurasian burbot, Lota lota was assessed at 4 and 30°C in seminal fluid, isotonic media (with and without Ca2+ ) and hypotonic media (with and without Ca2+ ). Spermatozoa were spontaneously activated in seminal fluid at 20°C and the maximum motility was recorded at 30°C, which is out of the spawning temperature range, indicating that no risk of activation occurs during routine semen handling in artificial insemination. Initiation of spermatozoon motility in L. lota is mediated by Ca2+ and sensitivity to Ca2+ is dependent on temperature.
Keywords: Sperm Motility; Calcium; osmolární koncentrace; vápník; mužské pohlaví; motilita spermií; zvířata; Semen; sperma; Gadiformes; Spermatozoa; Temperature; teplota; Osmolar Concentration; spermie; Male; Animals